Sedentarization as an adaptation to socio-environmental changes? Everyday herding practices in pastoralist communities in southern Ethiopia - Xin Wang; Chuan Liao; Sidney M. Brandhorst; Patrick E. Clark (Ecology and Society, 2022)
As humanity is faced with various changes in social-environmental systems, adaptation efforts have become increasingly important. Significant effort and resources have been spent on devising overarching, large-scale strategies in response to climate change and associated socioeconomic challenges. However, the mechanisms of adaptation employed by individuals and households in ordinary, daily life have received insufficient scholarly examination. This research aims to demonstrate the significance of everyday adaptation strategies of smallholder pastoralists who are on the front lines of changing socioeconomic regimes in East African drylands. We analyzed the daily spatiotemporal patterns of livestock behavior to understand everyday adaptation practices. Two different pastoralist communities in the Borana Zone in southern Ethiopia were compared, one of which keeps the traditional mobile pastoralism livelihood, while the other has sedentarized because of socio-environmental changes and policy incentives. The mobile pastoralists have larger grazing areas, and their cattle spend more time on foraging and resting. In contrast, the sedentarized pastoralists utilize the land near their settlements intensively and the cattle travel longer distances on average. Our findings suggest that sedentarization is a constrained adaptation strategy at best because it increases the recursive use of rangeland and its fragmentation and forces livestock to move more intensively on a daily and seasonal basis.